Proceedings of the 9th IEEE International Conference on Collaborative Computing: Networking, Applications and Worksharing 2013
DOI: 10.4108/icst.collaboratecom.2013.254213
|View full text |Cite
|
Sign up to set email alerts
|

A Social Trust Based Friend Recommender for Online Communities

Abstract: Recommendations to connect like-minded people can result in increased engagement amongst members of online communities, thus playing an important role in their sustainability. We have developed a suite of algorithms for friend recommendations using a social trust model called STrust. In STrust, the social trust of individual members is derived from their behaviours in the community. The unique features of our friend recommendation algorithms are that they capture different behaviours by (a) distinguishing betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Besides, there is recent work reporting significant recommendation performance improvement for social recommender systems [21,34,35,36,37,38,39]. On the other hand, there are also unsuccessful attempts at applying social recommendation [40,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, there is recent work reporting significant recommendation performance improvement for social recommender systems [21,34,35,36,37,38,39]. On the other hand, there are also unsuccessful attempts at applying social recommendation [40,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These two aspects are not considered in this article for the propagation. We refer readers to Nepal, Sherchan, and Paris (2011) and Nepal et al (2013b) for the comprehensive STrust model. For detailed analysis of the model and effect of various parameters on PopTrust, we refer readers to Nepal et al (2012Nepal et al ( , 2013a.…”
Section: Strust: a Social Trust Modelmentioning
confidence: 99%
“…Our current recommenders are built using our original trust model, which embodies explicit and implicit interactions among users (as it is based on users' behavior in the network). We have already conducted a series of evaluation experiments with these recommenders, comparing them to recommenders that exploit only explicit friendships among users (i.e., recommenders that exploit the social graph, considering direct friendships and "friends of a friend"-the FOAF concept) (Nepal et al 2013b;Nepal et al 2013c). These experiments showed that capturing implicit links (via the social trust concept) leads to performance improvements.…”
Section: Experiments With the Trust Propagation Modelmentioning
confidence: 99%
“…There is little evidence of other recommender systems which attempt to do this but work by Nepal et al [16] also focuses on recommendations to change user behaviour. They built a social rec-ommender for an online community to deliver government services to citizens.…”
Section: Related Workmentioning
confidence: 99%